2020
DOI: 10.1002/acm2.13053
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific quality assurance using machine log files analysis for stereotactic body radiation therapy (SBRT)

Abstract: An in-house trajectory log analysis program (LOGQA) was developed to evaluate the delivery accuracy of volumetric-modulated arc therapy (VMAT) for stereotactic body radiation therapy (SBRT). Methods have been established in LOGQA to provide analysis on dose indices, gantry angles, and multi-leaf collimator (MLC) positions. Between March 2019 and May 2020, 120 VMAT SBRT plans of various treatment sites using flattening filter-free (FFF) mode were evaluated using both LOGQA and phantom measurements. Gantry angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…This combination is particularly essential in meeting the resource intensive online ART program. Although our study found that the overall quality assurance of γ LV has significant correlation with γ AC, complement the other published works, 5,17 certain discrepancies between γ AC and γ LV were observed which were attributed to unaccounted factors in the log‐file fluence analysis, such as the couch transmission, measurement setup, and treatment planning system accuracy. For example, we found that in 1.5% of all the fields, γ AC was significantly lower than γ LV .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This combination is particularly essential in meeting the resource intensive online ART program. Although our study found that the overall quality assurance of γ LV has significant correlation with γ AC, complement the other published works, 5,17 certain discrepancies between γ AC and γ LV were observed which were attributed to unaccounted factors in the log‐file fluence analysis, such as the couch transmission, measurement setup, and treatment planning system accuracy. For example, we found that in 1.5% of all the fields, γ AC was significantly lower than γ LV .…”
Section: Discussionsupporting
confidence: 76%
“…During this study, we noticed the log‐file reported MLC positions significantly different, as much as 30 mm, from the plan positions which could amount to an order of magnitude larger than our institution experience 16 and other works. 3 , 6 , 17 , 18 After some investigations, it was found that the MLCs, outside the guard leaves or under the diaphragms, often had more than 1.0 mm discrepancy. Figure 4 shows an example of MLC leaf deviation of more than 30 mm (in red circle).…”
Section: Resultsmentioning
confidence: 99%
“…ICRU 142 suggested an action level of 1 mm gap width deviation [ 16 ]. Chow et al examined the VAMT plan for SBRT using log files, and found that the maximum MLC positional error was 0.6 mm [ 17 ]. Oliver et al analyzed the effect of MLC positioning errors for VMAT plans and concluded that the MLC positioning errors for VMAT treatments should be within 0.6 mm to keep the dose variation in the target coverage within 2% [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…20,22,23,32,37,38,43,45,50 In an attempt to validate log file-based QA systems, a number of authors have attempted to prove the sensitivity of log file-based QA to MLC position errors via a modification of treatment plan MLC positions to simulate leaf mispositioning. 32,41,42,48,50,55,56 However, it has been demonstrated via an electronic portal imaging device (EPID) imaging that log files can be insensitive to certain MLC positioning errors. 31,40,54 In the study of Agnew et al, 31 MLC position errors detected by the picket fence test were not evident in the log files.…”
Section: Introductionmentioning
confidence: 99%
“…Log file-based patient-specific QA usually involves the recalculation of the treatment plan with control points modified based upon log file data used as a representation of the "actual" delivery to be compared to the planned delivery. [23][24][25][26][27][28]32,[34][35][36][41][42][43][45][46][47][50][51][52]55 A number of authors have cautioned about the nonindependence of log files from the systems under investigation and potential insensitivity of log files to MLC mis-calibration or to faults in the MLC drive train and hence have suggested a need for separate MLC QA to assure log file accuracy. 20,22,23,32,37,38,43,45,50 In an attempt to validate log file-based QA systems, a number of authors have attempted to prove the sensitivity of log file-based QA to MLC position errors via a modification of treatment plan MLC positions to simulate leaf mispositioning.…”
Section: Introductionmentioning
confidence: 99%